Central America's Regional Trends and U.S. Cycles - Roache, Shaun (IMF Working Papers; Working Paper ;, 2008)
The economies of Central America share a close relationship with the United States, with considerable comovement of GDP growth over a long period of time. Trade, the financial sector, and remittance flows are all potential channels through which the U.S. cycle could affect the region. But just how dependent is growth in the region on the U.S.? Using the common cycles method of Vahid and Engle (1993), this paper suggests that the business cycle is dominated by the U.S.; region-specific growth drivers tend to be long-lasting shocks, rather than temporary fluctuations. The most cyclically sensitive countries include Costa Rica, El Salvador, and Honduras.